RETRACTED: Involvement of the 12th Grade English Language Textbook in Jordan: An analytical Study - Rami Ali Abu Sa'aleek (International Journal of Language Teaching and Education, 2018)
This article has been retracted/removal: please see IJoLTe publication etichs on duties of authors, section Multiple, Redundant or Concurrent Publication(https://online-journal.unja.ac.id/index.php/IJoLTE/Ethics) This article has been retracted/Remove at the request of the Editor-in-Chief of IRJE Journal, because the article previously has been published on that journal. If you want to get the article, please visit to: https://online-journal.unja.ac.id/irje/article/view/5909 International Journal of Language Teaching and Education takes a very strong view on this matter and apologies are offered to readers of the journal for this problems. Regards, IJoLTe Team